The Differential Impact of Reading Recovery on the Achievement of First Graders in the Newark School District, 1991-1993 - Ramaswami, Soundaram; Newark Board of Education, NJ. Office of Planning, Evaluation and Testing ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1994)
This evaluation assesses the impact of New Jersey's Reading Recovery program on first-grade students in the Newark School District. The report presents results from two cohorts and is divided into two main sections. Section 1 deals with the achievement of the students from the 1991-1992 academic year. Their performance at the end of first grade in both the Reading Recovery subtests and the Stanford Achievement Test is examined. In addition, the performance of these students at the end of second grade on the Stanford Achievement Test is presented. Section 2 provides results of the second cohort's (1992-1993 academic year) performance at the end of first grade on the Reading Recovery subtests and the standardized test. Evaluation results show that there was improvement in the performance levels of students in the skill areas tested and that reading levels were on par with or better than those of other students. (GLR)
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Achievement Rating; Achievement Tests; Compensatory Education; Early Intervention; Elementary School Students; Evaluation Methods; Grade 1.; High Risk Students; Higher Education; Inservice Teacher Education; Primary Education; Program Evaluation; Reading Difficulties; Reading Improvement; Reading Skills; Skill Development; Urban Education; Newark School System NJ -- Reading Recovery Projects; Reports, Descriptive